2017
DOI: 10.1007/978-3-319-52159-6_10
|View full text |Cite
|
Sign up to set email alerts
|

Text-Independent Speech Balloon Segmentation for Comics and Manga

Abstract: Abstract-Comics and manga are one of the most popular and familiar forms of graphic content over the world and play a major role in spreading country's culture. Nowadays, massive digitization and digital-born materials allow page-per-page mobile reading but we believe that other usages may be released in the near future. In this paper we focus on speech balloon segmentation which is a key issue for text/graphic association in scanned and digital-born comic book images. Speech balloons are at the interface betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…Liu et al [32] proposed a clump splitting based speech balloon localization method which can detect both closed and unclosed speech balloons. In addition, Liu et al [33] and Rigaud et al [34] proposed approaches making use of text contained in speech balloons for detecting speech balloon contours at pixel level. At such level of precision, it is also possible to localize and find the direction of the tail.…”
Section: Balloonsmentioning
confidence: 99%
See 4 more Smart Citations
“…Liu et al [32] proposed a clump splitting based speech balloon localization method which can detect both closed and unclosed speech balloons. In addition, Liu et al [33] and Rigaud et al [34] proposed approaches making use of text contained in speech balloons for detecting speech balloon contours at pixel level. At such level of precision, it is also possible to localize and find the direction of the tail.…”
Section: Balloonsmentioning
confidence: 99%
“…In Section 7, we have observed that traditional approaches [31][32][33][34] detect many false positive examples. However, although the deep learning model can localize very well the balloons, it cannot identify precisely the boundaries of the balloons as the traditional approaches.…”
Section: Refinement/cross-validation With Other Balloon Approachmentioning
confidence: 99%
See 3 more Smart Citations